Expression of a testis-specific hsp70 gene-related RNA in defined stages of rat seminiferous epithelium (The Rockefeller University Press, 1988)
Changes in the level of a testis-specific hsp70 gene-related transcript (hst70 RNA) and its cellular localization during the cycle of rat seminiferous epithelium have been investigated. Segments of seminiferous tubules at defined stages of the cycle were isolated in living condition by transillumination-assisted microdissection and the exact stages identified by phase-contrast microscopy of live cell squashes. The levels of the hst70 RNA were determined by Northern and slot blotting of whole cell lysates. High levels were found in stages XII-XIV and I to early VII of the cycle, and low levels were found in other stages, i.e., late VII (VIId) through VIII-XI of the cycle. The in situ hybridization revealed that the hst70 gene was activated in late pachytene primary spermatocytes during stage XII of the cycle, and that mRNA was then present in cells during differentiation through diakinesis, meiotic divisions, and early spermiogenesis (steps 1 through early 7). The activation of the gene coding for hst70 RNA shortly before meiotic divisions may indicate that the gene product is needed either during differentiation of late spermatocytes into spermatids or later during spermiogenesis, and that the mRNA may be stored in early spermatids.